Impact of internationalisation and innovation on balanced scorecard of Malaysian small and medium enterprises - Chong, Poh Ling (2019)
Small and medium enterprises (SMEs) represent the most significant portion of total business establishments in Malaysia. Nevertheless, they are noted with concern to fall short of prospective performance. One way to champion for excellent performance is through internationalisation. The global competition for outstanding performance in the perspectives of financial, customer, business processes, learning and growth, as well as the rapid increase in the rate of innovation advancement have made the business environment more competitive, and SMEs are no exception. Therefore, the current study looks at the importance of Internationalisation (INT) and Innovation (INN) on firm performance, which is measured by Balanced Scorecard (BSC) among Malaysian SMEs. The Revised Uppsala Internationalisation Process Model (RUIP Model) is accentuated, which specify INT as the core factor in enabling superior firm performance. Given limited empirical studies in this perspective, this study examined the mediating role of INN. Data collection was completed using survey method over half a year in 2018. A total of 404 responses were collected from business owners, managers and entrepreneurs of SMEs in Malaysia, and data were subjected to Structural Equation Modelling (SEM) analyses using AMOS software. Before conducting SEM, Exploratory Factor Analysis (EFA) was performed to scrutinise the underlying dimensions of INT, INN and BSC. The results show that although INT is positively related to INN, it is not directly related to BSC. Besides that, the results of each dimension of INT, which are Knowledge (KN), Trust (TR), Commitment (CM) and Opportunity Development (OD) shows all four are not positively related to INN. Furthermore, INN is found allied to BSC, while INN plays the mediating role between INT towards BSC. Besides, Country Policy (CP) tends to show the moderating role on INT towards BSC. This study integrates the Innovation-related Internationalisation Model (I-Model), Resource Based View Theory (RBV) and RUIP Model and establishes a research model for analysing SMEs’ performance. The study validated the mediating role of INN, and revealed the significant paths leading to superior firm performance. Since there is a dearth of conducting empirical studies previously that highlights INT for firm performance of Malaysian SMEs, therefore this research added value to the current level of knowledge in the existing literature. Overall, findings of this study provide useful insights to the owners, managers and entrepreneurs of Malaysian SMEs, as well as the Malaysian policymakers and regulators in identifying the requirements and solutions for pointing out the policy to strengthen the enterprise, maximise productivity and sustainable development.